Potentials of ribosomopathy gene as pharmaceutical targets for cancer treatment - Mengxin Wang; Stephen Vulcano; Changlu Xu; Renjian Xie; Weijie Peng; Jie Wang; Qiaojun Liu; Lee Jia; Zhi Li; Yumei Li (Journal of Pharmaceutical Analysis, 2024)
Ribosomopathies encompass a spectrum of disorders arising from impaired ribosome biogenesis and reduced functionality. Mutation or dysexpression of the genes that disturb any finely regulated steps of ribosome biogenesis can result in different types of ribosomopathies in clinic, collectively known as ribosomopathy genes. Emerging data suggest that ribosomopathy patients exhibit a significantly heightened susceptibility to cancer. Abnormal ribosome biogenesis and dysregulation of some ribosomopathy genes have also been found to be intimately associated with cancer development. The correlation between ribosome biogenesis or ribosomopathy and the development of malignancies has been well established. This work aims to review the recent advances in the research of ribosomopathy genes among human cancers and meanwhile, to excavate the potential role of these genes, which have not or rarely been reported in cancer, in the disease development across cancers. We plan to establish a theoretical framework between the ribosomopathy gene and cancer development, to further facilitate the potential of these genes as diagnostic biomarker as well as pharmaceutical targets for cancer treatment.